Identity, communication and modernity in Latin America - Martín-Barbero, Jesús (1989)
Since its inception, but especially since the mid-seventies, communication studies in Latin America have been torn between two issues: technology -the "technological fact" with its modernizing or developmentalist reason- and the current one, the question of memory and identities in their struggle to survive and reconstitute themselves from resistance and reappropriation. The uncertainty, the theoretical vacillation of these studies, their difficult translation into other "languages" has little to do with the ambiguity that a mestizo knowledge of two logics is loaded: that of knowledge regulated by laws of accumulation and compatibility, and of the re-knowledge of cultural differences and truths. That is why the theme of this conference concerns us in a very particular way to Latin Americans, because what is presented in it is not so much a question of actuality but the very fate of Latin American modernity, or better the plot of modernity and cultural discontinuities, of acronyms and utopias that sustains and resists, assimilates and confronts mass communication in our peoples.